INTEGRATION OF RELIGION AND SCIENCE IN SCIENCE SUBJECTS PRIMARY SCHOOL IN SEYYED HOSSEN NASR'S PERSPECTIVE - Barumun Parulian Hasibuan; Fujiwaty; Poltak Pembangunan Harahap; Pahri Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education is the most influential pillar in advancing a nation. It is the spearhead for the creation of reliable human resources in every country, especially Indonesia. The modernization of science sponsored by the Western world has led to a profound error, particularly in the crisis of faith in God, the creator of the universe. The shift in scientific principles after modernization has seen many changes in human characteristics, leading to rationality and materialistic attitudes. Amidst the crisis in religious values, awareness has re-emerged of the importance of a holistic educational approach, one that not only enlightens the mind but also touches the heart and shapes the soul based on religion. Seyyed Hossein Nasr emerged, criticizing modern science for erasing traces of God in the order of nature. This is where the idea of ​​sacralizing science emerged. Through Scientia Sacra, science can reveal its highly complex side, rich in sacredness and spirituality. Education that combines science and Islamic values ​​can help create individuals who are not only intellectually intelligent but also possess good morals. By studying Natural and Social Sciences (IPAS) in elementary schools, we can conclude how important the integration of religion and science is. This is in line with Nasr's opinion, in Islamic teachings, nature and humans are aspects that are separate entities, but are integral, holistic parts.